Bài 5: Những hằng đẳng thức đáng nhớ (Tiếp)

Nguyễn Việt Lâm
4 tháng 11 lúc 21:38
\(\left(xy+1\right)^2-\left(x+y\right)^2=\left(xy+1-x-y\right)\left(xy+1+x+y\right)\)\(=\left[y\left(x-1\right)-\left(x-1\right)\right]\left[x\left(y+1\right)+\left(y+1\right)\right]\)\(=\left(x-1\right)\left(y-1\right)\left(x+1\right)\left(y+1\right)\)b.\(\left(x+y\right)^3-\left(x-y\right)^3=\left(x+y-x+y\right)\left[\left(x+y\right)^2+\left(x-y\right)\left(x+y\right)+\left(x-y\right)^2\right]\)\(=2y\left(3x^2+y^2\right)\)c.\(3x^4y^2+3x^3y^2+3xy^2+3y^2=3x^3y^2\left(x+1\right)+3y^2\left(x+1\rig...
Đọc tiếp
Bình luận (0)
Ngô hải nam
4 tháng 11 lúc 21:42
a)\(=\left(xy+1-x-y\right)\left(xy+1+x+y\right)\)b)\(=x^3+3x^2y+3xy^2+y^3-\left(x^3-3x^2y+3xy^2-y^3\right)\)\(=x^3+3x^2y+3xy^2+y^3-x^3+3x^2y-3xy^2+y^3\)\(=x^3-x^3+3x^2y+3x^2y+3xy^2-3xy^2+y^3+y^3\)\(=6x^2y+2y^3=2y\left(3x^2+y^2\right)\)c)\(=3y^2\left(x^4+x^3+x+1\right)\)\(=3y^2\left[x^3\left(x+1\right)+\left(x+1\right)\right]\)\(=3y^2\left(x+1\right)\left(x^3+1\right)\)\(=3y^2\left(x+1\right)\left(x+1\right)\left(x^2-x+1\right)\)\(=3y^2\left(x+1\right)^2\left(x^2-x+1\right)=3y^2\left(x^2+2x+1\rig...
Đọc tiếp
Bình luận (0)
7A- Phú Dũng
4 tháng 11 lúc 21:39

a, (xy+1) mũ 2 -(x+y) mũ 2 =(xy+1-x-y).(xy+1+x+y) =[(xy-x)+(1-y)].[(xy+x)+(1+y)]=[x.(y-1)-(y-1)].[x.(y+1)-(y+1)]=(y-1).(x-1).(y+1).(x-1)=(x-1).[(y-1).(x-1)] dài thế :))

Bình luận (0)

Các câu hỏi tương tự
Nhu Bui
Xem chi tiết
Minh Lê Thị Hồng
Xem chi tiết
Linh Trần
Xem chi tiết
dmdaumoi
Xem chi tiết
Thị Phương Thảo Trần
Xem chi tiết

Khoá học trên OLM (olm.vn)


Khoá học trên OLM (olm.vn)